Characteristics of European adults who dropped out from the Food4Me Internet-based personalised nutrition intervention. Issue 1 (5th August 2016) - Livingstone, Katherine M; Celis-Morales, Carlos; Macready, Anna L; Fallaize, Rosalind; Forster, Hannah; Woolhead, Clara; O'Donovan, Clare B; Marsaux, Cyril FM; Navas-Carretero, Santiago; San-Cristobal, Rodrigo; Kolossa, Silvia; Tsirigoti, Lydia; et al.
Abstract: Objective: To characterise participants who dropped out of the Food4Me Proof-of-Principle study. Design: The Food4Me study was an Internet-based, 6-month, four-arm, randomised controlled trial. The control group received generalised dietary and lifestyle recommendations, whereas participants randomised to three different levels of personalised nutrition (PN) received advice based on dietary, phenotypic and/or genotypic data, respectively (with either more or less frequent feedback). Setting: Seven recruitment sites: UK, Ireland, The Netherlands, Germany, Spain, Poland and Greece. Subjects: Adults aged 18–79 years ( n 1607). Results: A total of 337 (21 %) participants dropped out during the intervention. At baseline, dropouts had higher BMI (0·5 kg/m 2 ; P <0·001). Attrition did not differ significantly between individuals receiving generalised dietary guidelines (Control) and those randomised to PN. Participants were more likely to drop out (OR; 95 % CI) if they received more frequent feedback (1·81; 1·36, 2·41; P <0·001), were female (1·38; 1·06, 1·78; P =0·015), less than 45 years old (2·57; 1·95, 3·39; P <0·001) and obese (2·25; 1·47, 3·43; P <0·001). Attrition was more likely in participants who reported an interest in losing weight (1·53; 1·19, 1·97; P <0·001) or skipping meals (1·75; 1·16, 2·65; P =0·008), and less likely if participants claimed to eat healthily frequently (0·62; 0·45, 0·86; P =0·003). Conclusions: Attrition did not differ between participants receiving generalised or PN advice but more frequent feedback was related to attrition for those randomised to PN interventions. Better strategies are required to minimise dropouts among younger and obese individuals participating in PN interventions and more frequent feedback may be an unnecessary burden.